Cost-Minimization of Availability of Fusidic Acid in the Treatment of Topical Infection in Iran - Meysam Seyedifar; Elahe Khorasani; Forouzan Taheri; Fatemeh Soleymani (Tehran University of Medical Sciences, 2018)
Background: Since at the time of this study fusidic acid was not available in the pharmaceutical market of Iran, this study was designed to investigate the economic aspects of the availability of fusidic acid for the treatment of topical infection in Iran. Methods: A decision tree model was used to compare circumstances, in which only mupirocin and fusidic acid were available. Medical and hospitalization costs were considered as direct medical costs. Budget impact analysis and sensitivity analysis were performed to examine the robustness of the base-case analysis. Results: It was assumed that a 50/50 ratio exists between burn patients to other patients. The treatment cost of 1000 cohort hypothetical patients was estimated at $54766 when mupirocin was the only available treatment choice and $15951 when fusidic acid was available as well. In other words, overall, $39 per patient was saved when physicians could consider fusidic acid as another choice of treatment. Conclusion: The availability of fusidic acid appears to be reasonable because it reduces the costs of skin infection treatment. It also improves antibiotic consumption appropriateness.